The relationship between dendritic branch dynamics and CPEB-labeled RNP granules captured in vivo - Bestman, Jennifer E.; Cline, Hollis (Frontiers in Neural Circuits, 2009)
Cytoplasmic Polyadenylation Element Binding protein (CPEB) is an RNA binding protein involved in dendritic delivery of mRNA and activity-dependent, polyadenylation-induced translation of mRNAs in the dendritic arbor. CPEB affects learning and memory and impacts neuronal morphological and synaptic plasticity. In neurons, CPEB is concentrated in ribonucleoprotein (RNP) granules that distribute throughout the dendritic arbor and localize near synapses. We tagged full-length CPEB and an inactive mutant CPEB, that is incapable of triggering activity-induced mRNA translation, with fluorescent protein, then imaged rapid dendritic branch dynamics and RNP distribution using 2-photon time-lapse microscopy of neurons in the optic tectum of living Xenopus laevis tadpoles. The density of CPEB-containing RNP granules in dendrites is high and the distribution of granules does not correlate with sites of rapid dendritic branch dynamics. Nevertheless, inactive CPEB accumulates in granules in terminal dendritic branches, supporting the hypothesis that upon activation CPEB and its mRNA cargo are released from granules and are then available for dendritic translation.